The Connotative Meaning from the Perspective of Roland Barthes' Semiotics (A Study on Khomr in the Qur'an) - Muhtarom Ali, Mohamad; Riadi, Abdul Kadir (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to analyze the connotative meaning of the term khomr in the Qur’an using Roland Barthes’ semiotic approach. This approach is employed to explore the layers of meaning that transcend the denotative dimension and to examine the relationship between signs and their socio-cultural context. The focus of this study is to trace the representation of khomr as a social and legal phenomenon in the Qur’anic text and its implications for shaping normative understanding among Muslims. The research data were collected through a literature review by examining Qur’anic verses related to khomr as well as classical and contemporary exegeses. The analysis reveals that khomr not only refers to intoxicating beverages in a physical sense but also carries connotative meanings reflecting mental, moral, and spiritual conditions. Roland Barthes’ semiotic perspective offers a conceptual framework for understanding the symbolism of khomr as a “modern myth” in contemporary Muslim society. These findings broaden insights into how the Qur’an constructs meaning through a system of signs and contribute theoretically to semiotic-based thematic exegesis studies.